Analysis Of Household Consumer Demand On Bulk Cooking Oil in Denpasar City - PUTRA, I MADE ADI DWIRANA; SUSRUSA, KETUT BUDI; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019, 2019)
Analysis Of Household Consumer Demand On Bulk Cooking Oil in Denpasar City Nowadays cooking oil is sold in two forms; one is referred to as bulk cooking oil ‘minyak goreng curah’ and the other is referred to as packaged cooking oil ‘minyak dalam kemasan’ with a particular trademark. However, the consumers in Denpasar still prefer the bulk cooking oil to the packaged cooking oil. This present study was intended to identify the factors contributing to the demand for the bulk cooking oil and the elasticity of the demand in Denpasar City. The study was conducted at Satrya Market, Sanglah Market, Kreneng Market, and Badung Market, which were all purposively determined. The samples were taken using the accidental sampling technique, totaling 40 and were purposively determined. This research uses Cobb-Douglas function with transformed data. The independent variables were X1 (the price of the bulk cooking oil), X2 (the price of the packaged cooking oil), X3 (the price of chicken), X4 (the number of family members), and X5 (the family income). The result of the model was as follows lnY = -5,876 – 2.184lnX1* + 3.588lnX2* - 0.332lnX3 + 0.311lnX4* + 0.244lnX5*. The factors which contributed to the demand for the bulk cooking oil were its price, the price of the packaged cooking oil, the price of chicken, the number of family members, and the family income. The price of the bulk cooking oil showed elasticity. The cross elasticity showed that the packaged cooking oil was a substitution commodity and that chicken was a complementary commodity. The income elasticity showed that the bulk cooking oil was an inferior commodity.